Avaliação da vulnerabilidade sísmica na realidade predial brasileira - Miranda, Paulo de Souza Tavares (2010)
Recent increases of earthquakes records in Brazil led to the publication of NBR 15421 (ABNT, 2006) - Design of seismic resistant structures - which provides the necessary requirements for security verification of structures in relation to the seismic actions. The recommendations of this code aim to reduce the seismic risk of new concrete structures. With regard to existing concrete structures it is necessary to study their seismic vulnerability. Among the various methods of seismic vulnerability assessment found in literature, the Hirosawa method, more precisely its first level of screening procedure, was chosen to be adapted to the Brazilian reality and make a large scale application. In the adaptation process of the method are initially studied the parameters of the Brazilian design of seismic resistant structures code and a comparison with the American codes, IBC (ICC, 2006) and SEI7 (ASCE, 2005), is carried out. The study of Hirosawa method allowed the identification of the necessary adjustments to adapt the method considering the NBR 15421 (ABNT, 2006) requirements and local constructive characteristics. The adapted method was applied to a single degree of freedom system and to four model structures varying the number of floors and structural configuration in terms of horizontal and vertical irregularity. The model structures intend to represent essential building occupancy. Each one of the structures was analyzed assuming their exposure to all seismic design accelerations and being settled in any site class covered in NBR 15421 (ABNT, 2006). The results are presented in tables, graphs and maps of seismic vulnerability. No model structures presented seismic vulnerability in seismic zone 0; settled in site class E, all model structures presented seismic vulnerability in seismic zones 2, 3 and 4; and the regular structures showed better seismic performance. The meaning of vulnerability exposed in this work is not related to the mandatory off the building, but rather the need for more detailed and complex analysis of the expected behavior of these buildings under a seismic event.